Extraction, physicochemical properties and antioxidant activities of xanthone from mangosteen (Garcinia mangostana Linn.) pericarp - Aboutorab, Nasrin (2017)
Garcinia mangostana Linn. (mangosteen) belongs to the Guttiferae family; about 2/3 of the fruit weight is pericarp which is thrown out as a waste by the fruit processing industries due to its unpleasant astringency taste, while they are a great source of bio-actives such as polyphenols and xanthones. Extraction and utilization of these bioactive compounds from the fruit pericarp will be valuable for the fruit industries. Even though the extraction of bioactive compounds was done previously; utilization and further enhancement of those bioactive compounds in the functional product development is still in the budding stage. Owing to the above concern, the first purpose of the present study is to investigate the effect of drying and extraction procedure (solvent used, ultrasound pretreatment, and their combination) on the extraction yield, antioxidant activity, and the levels of total polyphenol compounds (TPC), total xanthones, and α- mangostin. The second purposes is to encapsulate the xanthone crude extract isolated from mangosteen fruit pericarp powder (MFPP), with maltodextrin at various conditions. The study showed the maximum TPC value (322.86 ± 8.31 mg GAE/g MFPP), α- mangostin (42.233 ± 2.072 mg/g MFPP), high total xanthone (89.360 ± 1.02 mg/ g MFPP), and DPPH radical scavenging activity (120.534 ±6.526 mM TE /100g MFPP) for ethanol extract of freeze dried MFPP. Furthermore, using 57% ethanol, 5 min direct sonication, 50 % pulser as a pretreatment and 51min solvent extraction resulted in isolating xanthone crude extract containing high amount of α-mangostin (54.633mg/100mg of total xanthone), and total xanthone (115.394 mg/g DW) with optimum TPC (560.518 mg GAE/g MFPP) value and DPPH value (176.785 mM TE/100g MFPP). The MFPP extract can be efficiently encapsulated with maltodextrin at ratio 2.5: 1, 150°C inlet temperature, and flow rate 15 rpm (10 mL/min). The characteristics of the powder encapsulated xanthone crude extract (XCEP) are particle size: 62.95 to 86.98μm (D[4,3]- volume weighted), encapsulation yield 62%, tap density:0.201 mg/mL,hygroscopicity:10.17%, water activity (WA): 0.279, moisture content: 3.44%, water absorption index (WAI): 0.409, water solubility index (WSI): 84.43g/100g, thermal glass transition temperature (Tg° C) : 158.507° C, TPC retention:70%, DPPH radical scavenging activity: 661.83mM TE/g powder, total xanthone: 563.520 mg/g powder and α-mangostin content: 73.910 mg/ g powder. Using encapsulation with spray drying, more than 90% of TPC, total xanthone and α-mangostin was remained unchanged and 85% of antioxidant activity was still hold after 60 days incubation at 4°C and room temperature. Supplemented milk with microencapsulated xanthone crude extract shows good functional properties such as high TPC (319.32mg GAE/ 200mL milk) and DPPH value (298.76 mM TE/200mL milk) comparing to the TPC value of 99.549 mg GAE/ 200mL milk and DPPH value of 35.44 mM TE/200mL milk for control milk during 16 days at 4° C. As a conclusion, microencapsulated xanthone crude extract showed stable physicochemical and functional properties during long-term storage in form of powder or as supplement into milk. Together these results provide important visions to the potential of encapsulated xanthone crude extract to be used as supplement and application as bioactive compounds in the functional product development.